h y Ailsa Wallace. - Wallace, Ailsa, 1977- (Oxford : Oxford University Press, 2009)
Zur Muhlen saw literature primarily as a political tool and used popular forms of literature to convey her ideas to a wide audience. This book examines her prose fiction against the backdrop of her life and the turbulent times she lived in - the Weimar Republic and exile from the Third Reich.
Description based on print version record.
Includes bibliographical references and index.
Keywords: d; Austrian fiction -- 20th century -- History and criticism; Socialism in literature; Politics in literature